Pengaruh Partisipasi Anggaran terhadap Kinerja Manajerial - Muhammad Habibie - (JEBIM Prima, 2020)
Participation encourages every manager to improve performance (performance) which in turn can increase organizational effectiveness. The budget is an estimate of the performance that will be obtained during a certain period which is expressed in financial terms. The research objective was to determine the effect of budget participation on managerial performance.he population of this research is the manager and assistant manager of PT. Bahari Samudera Sentosa (BSS) as many as 16 people and PT. Bahari Mandiri Brothers (BMB) as many as 18 people so that the total population is 34 people and the sample is the total population.Data were analyzed using regression analysis to answer the research hypothesis.The results showed that there was an effect of budget participation on managerial performance.